2021
DOI: 10.3390/jcm10215107
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Sarcopenia in Metastatic Colorectal Cancer Patients Treated with Trifluridine/Tipiracil

Abstract: Sarcopenia is common in metastatic colorectal cancer (mCRC), increases the risk of treatment-related toxicity and reduces survival. Trifluridine/tipiracil (TT) chemotherapy significantly improved survival in refractory mCRC patients, but the prognostic and predictive role of pretherapeutic sarcopenia and variation in the skeletal muscle index (SMI) during this treatment has not been investigated so far. In this retrospective, observational study, clinical data on mCRC patients treated with TT at six cancer cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Table 1 presents the baseline characteristics of the included studies. Among the studies published between 20 16 and 2022, 8 studies [ 27 29 , 37 , 40 , 42 , 45 , 46 ] were from Asia, 7 studies [ 39 , 41 , 43 , 44 , 47 49 ] were from Europe and a separate study [ 38 ] from Brazil. All of the studies were retrospective cohort, and 68.75% of the included studies (11/16) were of high quality with an NOS score of ≥ 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the baseline characteristics of the included studies. Among the studies published between 20 16 and 2022, 8 studies [ 27 29 , 37 , 40 , 42 , 45 , 46 ] were from Asia, 7 studies [ 39 , 41 , 43 , 44 , 47 49 ] were from Europe and a separate study [ 38 ] from Brazil. All of the studies were retrospective cohort, and 68.75% of the included studies (11/16) were of high quality with an NOS score of ≥ 7).…”
Section: Resultsmentioning
confidence: 99%
“…During this process, we excluded 688 irrelevant citations and 68 potentially relevant studies were selected for full-text review. Due to non-population-based cohorts, reviews, meta-analyses or no outcome data reported, 16 studies [27][28][29][37][38][39][40][41][42][43][44][45][46][47][48][49] involving 1,675 participants satisfied the inclusion criteria and were eligible to be included in the final metaanalysis (Fig. 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Seven designs defined endpoint CT timing using a set number of chemotherapy cycles, ranging from one to six cycles; however, the length of one cycle was not often reported 23,34,40,50,51,54,55 . Ten designs specified a treatment or disease milestone as the endpoint, including first reassessment, 30,31,43,53 progression 18,44,49,52 and last CT 36,46 . Non‐specific descriptors for the endpoint, such as ‘during treatment’ or ‘after treatment’, were applied in five designs 24,27,35,38,48 .…”
Section: Study Design: Scan Timing and Intervalsmentioning
confidence: 99%
“…The relationship between SM change and chemotherapy toxicity was explored in eight studies. Of these, five publications compared the incidence of treatment toxicities between ‘SM losers’ and ‘SM non‐losers’ (i.e., univariable), 25,27,31,32,40 and three included SM loss in multivariable logistic regression to predict odds of toxicity 22,29,50 . The relationship between SM loss and changes in health‐related quality of life or physical function was explored in four studies 19,39,40,59 …”
Section: Application Of Skeletal Muscle and Adipose Change To Clinica...mentioning
confidence: 99%
“…In addition to oncological factors and treatment factors, the outcomes of cancer treatment are greatly influenced by host factors, such as the nutritional status, immune status, systemic inflammation, and intestinal flora (1)(2)(3)(4)(5)(6). Malnutrition has been reported to be associated with shorter survival time after curative surgery and worse chemotherapeutic efficacy in patients with various gastrointestinal malignancies (7)(8)(9)(10)(11). In our previous study, the prognostic nutritional index (PNI), which was calculated based on the serum albumin concentration and peripheral lymphocyte count, was found to be correlated with the chemotherapeutic outcomes in patients with unresectable metastatic colorectal cancer (12).…”
mentioning
confidence: 99%